Elastic optical network for fragmented bandwidth allocation with limited slicers - Kaito Akaki; Praphan Pavarangkoon; Nattapong Kitsuwan (My University, 2021)
A fragmentation problem increases bandwidth blocking in an elastic optical network (EON). A technique to reduce bandwidth fragmentation is important. The routing and spectrum allocation (RSA) approach is one of the techniques to reduce bandwidth fragmentation. A slicing-and-stitching technology is adopted in EON to relax a consecutive slot constraint for the spectrum allocation process. A slicer is used to split a signal of a spectrum band into several spectrum components, as a slicing process. The split spectrum components are transmitted to the destination before recovering the original signal at the destination, as a stitching process. An RSA algorithm for EON with this technology is applied. As a result, the request blocking is reduced. Slicers are applied to all nodes in the network. The implementation cost is high. Reducing the number of slicers in the network degrades the performance in terms of bandwidth blocking. This paper investigates bandwidth blocking when the number of slicers is limited. Some nodes in the network are selected to place slicers. A betweenness centrality (BC) value is used to select the nodes to place the slicers. The result from a simulation shows that placing a small number of slicers per node for a large number of nodes has better performance than placing a large number of slicers per node for a small number of nodes.
Keywords: Advanced Optical Network Technologies; Optical Network Technologies; Advanced Photonic Communication Systems